Commemorating the Unexperienced: The Strategical Function of Jean Améry’s Memories in the Postmemorial Novel Morbus Kitahara by Christoph Ransmayr - Henke, Daniela (Status Quaestionis, 2020)
The article examines the novel Morbus Kitahara by Christoph Ransmayr from the viewpoint of the postmemorial dilemma: how to commemorate someone else’s experiences that are relevant for one’s own identity without appropriating them? The article argues that this novel shows an awareness for the sublime character and sanctity of Holocaust testimonies, while at the same time demonstrating strategies to solve the dilemma. Intertextuality, body narration and the usage of direct speech are the novel’s three cornerstones that constitute an attentive manner of commemorating what was not directly experienced. The key reference point that the novel provides for postmemorial remembrance is its connection with Jean Améry’s autobiographical and philosophical works.